Amphoras from an early imperial shipwreck at Fig Tree Bay, Cyprus: International imports and local imitations - Leidwanger, Justin (Rei Cretariae Romanae Fautorum Acta, 2024)
Shallow-water survey off the southeast coast of Cyprus has brought to light considerable evidence for exchange of agricultural materials in transport ceramics, with particularly high levels of maritime activity during the Roman and Late Roman centuries. The present discussion focuses on a late 1st- or early 2nd-century cargo that probably represents a typical small merchant vessel carrying a mixed cargo in several amphora types: “Pseudo-Cos en cloche” jars of possible Cilician origin, Gauloise 4 amphoras and (Cilician?) imitations, and another bifid-handle amphora of unknown origin. The Fig Tree Bay wreck provides a useful closed assemblage for dating these better and lesser-known types, and a valuable window into the dynamics of a small scale trade that brought both local and international goods to a quiet Roman province. Moreover, when understood within a broader socioeconomic context, the imitation and adaptation of the Gauloise 4 form documented here may hint at a potential internationalism in marketing of Gaulish-style agricultural products in the eastern mediterranean.